Pelvic Reconstruction With a Novel Three-Dimensional-Printed, Multimodality Imaging Based Endoprosthesis Following Enneking Type I + IV Resection - Yu, Zeping; Zhang, Wenli; Fang, Xiang; Tu, Chongqi; Duan, Hong (Frontiers in Oncology, 2021)
Background and purpose: Pelvic tumor involving Type I + IV resections are technically challenging, along with various reconstructions methods presenting unsatisfactory outcomes and high complication rates. Since predominating studies preferred adopting pedicle screw-rod system (PRSS) to address this issue, we designed a novel three-dimensional-printed, multimodality imaging based endoprosthesis with patient-specific instrument assistance to facilitate the surgical reconstruction of pelvic tumor involving Enneking Type I + IV resection. We aimed to investigate the clinical effectiveness of this novel endoprosthesis and compare it with PRSS in Type I + IV reconstruction. Methods: We retrospective studied 28 patients for a median follow-up of 47 months (range, 10 to 128 months) in this study with either 3D-printed endoprosthesis reconstruction (n = 10) or PRSS reconstruction （n = 18） between January 2000 and December 2017. Preoperative three-dimensional multimodality imaging technique including three-dimensional computed tomography, contrast-enhanced CT angiography, contrast-enhanced magnetic resonance imaging, and neurography was used for tumor evaluation, PSI design, virtual surgery, and endoprosthesis fabrication. Operative duration, blood loss, resection margins, functional assessments, and complications were analyzed between two groups. Results: Minor surgical trauma with mean operative duration of 251 ± 52.16 minutes (p = 0.032) and median intraoperative hemorrhage of 2000ml (range, 1600, 4000ml) (p = 0.032) was observed in endoprosthesis group. Wide margins were achieved in 9 patients of endoprosthesis group compared with 10 in PRSS group (p = 0.09). The 1993 version of the Musculoskeletal Tumor Society score (MSTS-93) was 23.9 (range, 15 to 28), which was higher than 19.83 (range, 10 to 26) (p = 0.012). The median limb discrepancy was minor in endoprosthesis group 1.5cm (range, 1, 2cm) (p = 0.03). The complication included superficial wound infection in two patients and dislocation of the hip in one patient. Conclusion: The novel design of this 3D-printed endoprosthesis, together with 3DMMI and PSI assisted, is technically accessible with favorable clinical outcomes. Further study is essential to identify its long-term outcomes.